2022
DOI: 10.1001/jamainternmed.2022.0189
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Ivermectin Treatment on Disease Progression Among Adults With Mild to Moderate COVID-19 and Comorbidities

Abstract: IMPORTANCEIvermectin, an inexpensive and widely available antiparasitic drug, is prescribed to treat COVID-19. Evidence-based data to recommend either for or against the use of ivermectin are needed. OBJECTIVE To determine the efficacy of ivermectin in preventing progression to severe disease among high-risk patients with COVID-19. DESIGN, SETTING, AND PARTICIPANTS The Ivermectin Treatment Efficacy in COVID-19 High-Risk Patients (I-TECH) study was an open-label randomized clinical trial conducted at 20 public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
69
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 34 publications
0
69
0
3
Order By: Relevance
“…Ivermectin is an effective antiparasitic with multiple proposed mechanisms of action against SARS-CoV-2, including inhibition of viral transfer and replication in vitro and anti-inflammatory effects based on prior studies of other viruses (e.g., Zika, Dengue) [ [146] , [147] , [148] , [149] , [150] ]. Current evidence based on higher quality data suggests no benefit [ [151] , [152] , [153] ]. While several early studies suggested reduced mortality, shortened recovery time, and decreased transmissibility benefits with ivermectin in the treatment of COVID-19 patients, these studies suffered from major limitations, including wide heterogeneity, poor subject allocation, limited or no blinding, and inadequate controls with risk of confounding [ 10 , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ivermectin is an effective antiparasitic with multiple proposed mechanisms of action against SARS-CoV-2, including inhibition of viral transfer and replication in vitro and anti-inflammatory effects based on prior studies of other viruses (e.g., Zika, Dengue) [ [146] , [147] , [148] , [149] , [150] ]. Current evidence based on higher quality data suggests no benefit [ [151] , [152] , [153] ]. While several early studies suggested reduced mortality, shortened recovery time, and decreased transmissibility benefits with ivermectin in the treatment of COVID-19 patients, these studies suffered from major limitations, including wide heterogeneity, poor subject allocation, limited or no blinding, and inadequate controls with risk of confounding [ 10 , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] ].…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence based on higher quality data suggests no benefit [ [151] , [152] , [153] ]. While several early studies suggested reduced mortality, shortened recovery time, and decreased transmissibility benefits with ivermectin in the treatment of COVID-19 patients, these studies suffered from major limitations, including wide heterogeneity, poor subject allocation, limited or no blinding, and inadequate controls with risk of confounding [ 10 , [146] , [147] , [148] , [149] , [150] , [151] , [152] , [153] ]. Additionally, many studies employed dosing regimens larger than those previously approved for parasitic infections, increasing the risks of side effects [ 10 , 148 , 152 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly clinically significant benefits are cited as evidence that ivermectin does not work for COVID-19 because the results were not statistically significant. In a recent study [3], ivermectin was added to standard care for 241 participants while standard care was provided to 249 participants. The authors concluded that, "The study findings do not support the use of ivermectin for patients with COVID-19."…”
Section: A Negative Study Of Ivermectinmentioning
confidence: 99%
“…The proteins are dynamic molecules ( Laage et al, 2017 , Lee, 1983 ), and at thermal equilibrium, the intrinsic volume (geometric component) and the hydration or interaction volume are constantly fluctuacting around their mean values and Laage et al, 2017 , Lee, 1983 , Lee, 1983 , Liang et al, 2020 , Lim et al, 2022 , Lindow et al, 2013 , Lockbaum et al, 2021 .The structural dynamic is very important for biological function of protein and stability ( Lee, 1983 , Lockbaum et al, 2021 , Low et al, 2022 , Luong et al, 2015 , Macchiagodena et al, 2022 , Madhavi et al, 2021 , Mahdian et al, 2021 , Marchi, 2003 , Mejía-Tamayo et al, 2018 , Monkos, 2013 ). The intrinsic protein flexibility is relevant to interaction with ligand and can contribute to the binding process ( Lindow et al, 2013 , Lockbaum et al, 2021 , Monkos, 2004 , Mori et al, 2006 , Morris et al, 2009 , Osipiuk et al, 2021 , O’Boyle et al, 2011 ).…”
Section: Theorymentioning
confidence: 99%